Renal stones. (January 2019) - Viljoen, Adie; Chaudhry, Rabia; Bycroft, John
Renal stone disease is a worldwide problem which carries significant morbidity. It frequently requires specialist urology intervention. Patients with recurrent disease and those at high risk require specialist investigations and review. Certain cases benefit from medical and surgical intervention. In this review, we discuss the pathophysiology, risk assessment, specialist investigations and various interventions, their rationale and evidence base. This review aims to provide an update of the previous publication in 2001 in this journal on this topic.